2014
DOI: 10.1111/and.12362
|View full text |Cite
|
Sign up to set email alerts
|

Sperm aneuploidy in infertile male patients: a systematic review of the literature

Abstract: Males with abnormal karyotypes and subgroups of fertile and infertile males with normal karyotypes may be at risk of producing unbalanced or aneuploid spermatozoa. Biological, clinical, environmental and other factors may also cause additional sperm aneuploidy. However, increased risk of sperm aneuploidy is directly related to chromosomally abnormal embryo production and hence to poor reproductive potential. This systemic literature review focuses on the identification of these males because this is an essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 167 publications
0
21
0
5
Order By: Relevance
“…Although oocytes have an intrinsic capacity to reverse DNA damage (Kumar et al, 2012), the positive association demonstrated in this meta-analysis suggests that an elevated sDF reflects a high degree of sperm damage in couples with RPL that may be beyond the repair capacity of the oocyte, thereby giving rise to genetic mutations that are incompatible with post-implantation embryonic development and ongoing pregnancy. Notably, several recent studies have also demonstrated that sperm aneuploidy may be an important cause of elevated sDF, thereby supporting a potential role for preimplantation genetic testing in cases of unexplained RPL (Chatziparasidou et al, 2015;Esquerre-Lamare et al, 2018). In this way, sDF may hold significant diagnostic capability, and the elevated sperm fragmentation found in men of couples with RPL suggests the involvement of a male factor in the pathogenesis of RPL.…”
Section: Discussionmentioning
confidence: 91%
“…Although oocytes have an intrinsic capacity to reverse DNA damage (Kumar et al, 2012), the positive association demonstrated in this meta-analysis suggests that an elevated sDF reflects a high degree of sperm damage in couples with RPL that may be beyond the repair capacity of the oocyte, thereby giving rise to genetic mutations that are incompatible with post-implantation embryonic development and ongoing pregnancy. Notably, several recent studies have also demonstrated that sperm aneuploidy may be an important cause of elevated sDF, thereby supporting a potential role for preimplantation genetic testing in cases of unexplained RPL (Chatziparasidou et al, 2015;Esquerre-Lamare et al, 2018). In this way, sDF may hold significant diagnostic capability, and the elevated sperm fragmentation found in men of couples with RPL suggests the involvement of a male factor in the pathogenesis of RPL.…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, the assessment of chromosomal aneuploidies in spermatozoa before ART is useful to predict pregnancy outcomes and help genetic counsellor to support the couples. The correlation between sperm aneuploidy and sperm concentration has been widely considered (Chatziparasidou, Christoforidis, Samolada, & Nijs, ). In the present work, sperm concentration was negatively and weakly correlated with disomy Y, which could be explained by the observations of Brugnon et al, , who described a high expression of apoptotic markers on the surface of spermatozoa with chromosomal abnormalities causing oligozoospermia due to apoptosis process (Brugnon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the meiotic recombination-dependent mis-segregation of X and Y chromosomes is a known cause of male infertility in otherwise karyotipycally normal men [65]. More generally, sperm aneuploidy of the sex chromosomes affects fertile men as well, though without impairing their ability to procreate [66]. The phenotype of 47,XYY subjects is generally almost normal, except for a slightly taller stature, variable cognitive disorders and, more rarely, motor skill impairment [60,67,68].…”
Section: Disomy Of the Ymentioning
confidence: 99%